Dysregulated protocadherin-pathway activity as an intrinsic defect in induced pluripotent stem cell–derived cortical interneurons from subjects with schizophrenia - Shao, Zhicheng; Noh, Haneul; Bin Kim, Woong; Ni, Peiyan; Nguyen, Christine; Cote, Sarah E.; Noyes, Elizabeth; Zhao, Joyce; Parsons, Teagan; Park, James M.; Zheng, Kelvin; Park, Joshua J.; et al. (Nature neuroscience, 2019)
We generated cortical interneurons (cINs) from induced pluripotent stem cells derived from 14 healthy controls and 14 subjects with schizophrenia. Both healthy control cINs and schizophrenia cINs were authentic, fired spontaneously, received functional excitatory inputs from host neurons, and induced GABA-mediated inhibition in host neurons in vivo. However, schizophrenia cINs had dysregulated expression of protocadherin genes, which lie within documented schizophrenia loci. Mice lacking protocadherin-α showed defective arborization and synaptic density of prefrontal cortex cINs and behavioral abnormalities. Schizophrenia cINs similarly showed defects in synaptic density and arborization that were reversed by inhibitors of protein kinase C, a downstream kinase in the protocadherin pathway. These findings reveal an intrinsic abnormality in schizophrenia cINs in the absence of any circuit-driven pathology. They also demonstrate the utility of homogenous and functional populations of a relevant neuronal subtype for probing pathogenesis mechanisms during development. Shao et al. report that interneurons derived from iPSCs from schizophrenia patients have altered protocadherin expression and synaptic and arborization deficits. A PKC inhibitor, acting downstream of protocadherin, reversed the arborization deficit.